Integration of Vehicle-to-Grid (V2G) Technology for Renewable Energy Storage and Grid Stability - Kulat, H. S.; Waghmare, T.T.; D Dalvi, Gopalkrishna; Burje, Shrikant (Journal of Neonatal Surgery, 2025)
The integration of Vehicle-to-Grid (V2G) technology represents a transformative solution for enhancing renewable energy storage and ensuring grid stability. With increasing penetration of intermittent renewable sources such as solar and wind, the power grid faces significant challenges in balancing supply-demand fluctuations. V2G systems allow bidirectional energy flow, enabling Electric Vehicles (EVs) to serve not only as loads but also as distributed storage assets. Technically, this involves the use of advanced bidirectional chargers, smart metering, and communication protocols compliant with standards such as ISO/IEC 15118 and IEEE 2030.5. From a systems perspective, aggregated EV fleets can provide ancillary services including frequency regulation, peak shaving, voltage support, and spinning reserve. Studies indicate that a penetration of 20–30% EVs with V2G capabilities can reduce peak demand by up to 15% and enhance renewable energy utilization by 25%. Integration also supports reduction of carbon emissions, with estimates suggesting up to 40 MtCO₂/year savings in regions adopting large-scale V2G deployment. Advanced optimization techniques, such as model predictive control (MPC) and AI-driven scheduling, further improve charging/discharging efficiency. Global policies, including the European Union’s Green Deal and the U.S. Department of Energy’s EV Everywhere initiative, are actively promoting V2G-enabled smart grids. Technical pilot projects, such as the UK’s Powerloop and Japan’s Nissan LEAF-to-Grid trials, have demonstrated the feasibility of V2G in real-world conditions. However, challenges remain in terms of battery degradation, interoperability of charging standards, and grid cybersecurity. Overall, V2G technology provides a robust pathway to achieving sustainable, resilient, and flexible power systems in the era of renewable energy integration.